Characterisation of the influenza virus matrix protein M1 and its role in oligomerisation - Mohd Kipli, MFH (2020)
Influenza matrix protein 1 (M1) is the most abundant protein in the virus and forms the matrix layer beneath the lipid bilayer of the viral capsid, stabilising and providing shape to the three-dimensional structure of the virus particles. As a matrix protein, it is crucial for M1 to be able to associate and dissociate at the right stages of the influenza A virus life cycle. M1 polymerises upon binding to membranes. However, the physical triggers that covert M1 from a water-soluble component in the nucleus to an immobilised lattice of helical polymer on the membrane surface are still poorly understood. M1 oligomerisation correlates with pH, assembling at a high pH and disassembling at a low pH, which is driven primarily by the N-terminal domain (M1NT). In this thesis, the structural plasticity and oligomerisation of M1NT in solution was studied using NMR spectroscopy. We showed that M1NT was pertubed by sterol-containing compounds which induce a conformational change facilitating self-association in a pH dependent manner. The perturbed residues were consistent with the stacked-dimer interface, which are exposed at the surface and most sensitive to sterols. The effects of sterols on this interface is indirect and they most likely exert their effects through a reduction in water activity. The local changes observed are consistent with a priming of the N-terminal domain for polymerization. The exposed surface of the M1NT interface is hypothesised to be sensitive to changes in its environment and may serve to regulate polymerisation of M1 at the membrane surface. Chemical shift perturbations data and crystal structure models indicate the effects of conformational changes can be propagated from one subdomain interface to another.